PERAN PENYIDIK ANAK DALAM MELAKUKAN PENYIDIKAN TERHADAP ANAK PELAKU TINDAK PIDANA - Dahlia, Roza (Ensiklopedia Sosial Review, 2019)
Criminal cases carried out by children in general the provisions violated are criminal regulations contained in the Criminal Code, then the investigation is carried out by general investigators in this case the National Police investigator. In line with the enactment of the Law on the Criminal Justice System for Children, it has been confirmed that the investigation of cases of naughty children was carried out by police investigators on the basis of law Article 26 paragraph (1) Number 11 of 2012 concerning the Criminal Justice System which states that an investigation of a child case is carried out by an Investigator determined based on the Decree of the Head of the Indonesian National Police or another official appointed by the Head of the Indonesian National Police. The purpose of this study is to look at the role of child investigators in conducting investigations of child offenders. The research method used in this study is a normative juridical research method. Not all police investigators can investigate bad boy cases. The Child Criminal Justice System Law is known for the existence of child investigators, who are authorized to conduct investigations. Child investigators are appointed by the National Police Chief with a Special Decree for these purposes. The Child Criminal Justice System Law through Article 26 Paragraph (3) sets out the conditions that must be fulfilled by an Investigator.